2004
DOI: 10.1038/sj.onc.1207734
|View full text |Cite
|
Sign up to set email alerts
|

Role of the putative tumor metastasis suppressor gene Drg-1 in breast cancer progression

Abstract: The differentiation-related gene-1 (Drg-1) was first identified as a gene strongly upregulated by induction of differentiation in colon carcinoma cells in vitro, and later the same gene was shown to suppress tumorigenicity of human bladder cancer cells in vivo. On the other hand, we and others have demonstrated that the Drg-1 gene suppresses prostate and colon cancer metastases in mouse models. In the context of such potential organ-specific differential function of the Drg-1 gene, the present study was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
167
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(193 citation statements)
references
References 11 publications
21
167
2
3
Order By: Relevance
“…The function of this protein remains unclear, and some controversy regarding its role in cancer exists. Some studies suggest NDRG1 involvement in metastatic suppression, whereas others show higher expression of this protein, likely related to metastasis (51)(52)(53)(54)(55). The difference in subcellular localization of NDRG1 may be important for its function, and we therefore remain open to the concept that it plays some role in the development of metastases.…”
Section: Discussionmentioning
confidence: 98%
“…The function of this protein remains unclear, and some controversy regarding its role in cancer exists. Some studies suggest NDRG1 involvement in metastatic suppression, whereas others show higher expression of this protein, likely related to metastasis (51)(52)(53)(54)(55). The difference in subcellular localization of NDRG1 may be important for its function, and we therefore remain open to the concept that it plays some role in the development of metastases.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, NDRG1 was found to be negatively correlated with tumor progression, while being positively correlated with better patient prognosis for a range of cancers, including those of the prostate, breast, colon, and pancreas (5,(11)(12)(13)16). Considering the potential therapeutic implications of utilizing NDRG1 as a molecular target for the treatment of cancer, the molecular mechanisms by which NDRG1 is able to exert its anti-cancer effects have recently become the subject of intense research.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies examining the prognosis of patients with these latter neoplasms demonstrated that those with higher NDRG1 levels had a significantly better outcome when compared with those with low NDRG1 levels (5,(11)(12)(13). Hence, NDRG1 is a promising prognostic indicator and molecular target for these cancers (14), which represent some of the most common and fatal neoplastic conditions.…”
mentioning
confidence: 99%
“…Overexpression of NDRG1 in vitro results in morphological changes typical of cell differentiation and is inversely related to tumour growth and metastasis (Kurdistani et al, 1998;Guan et al, 2000;Bandyopadhyay et al, 2003;Bandyopadhyay et al, 2004a). Furthermore, its expression is increased by the tumour suppressor proteins p53 and PTEN (Kurdistani et al, 1998;Bandyopadhyay et al, 2004b) and clinical data have shown that its presence is statistically correlated with an increased survival of patients diagnosed with prostate cancer or liver metastasis from colorectal cancers (Bandyopadhyay et al, 2003;Shah et al, 2005).…”
mentioning
confidence: 99%